2004
DOI: 10.1128/jvi.78.2.834-840.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nipah Virus: Vaccination and Passive Protection Studies in a Hamster Model

Abstract: Nipah virus, a member of the paramyxovirus family, was first isolated and identified in 1999 when the virus crossed the species barrier from fruit bats to pigs and then infected humans, inducing an encephalitis with up to 40% mortality. At present there is no prophylaxis for Nipah virus. We investigated the possibility of vaccination and passive transfer of antibodies as interventions against this disease. We show that both of the Nipah virus glycoproteins (G and F) when expressed as vaccinia virus recombinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
182
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(188 citation statements)
references
References 26 publications
4
182
0
2
Order By: Relevance
“…22,87 A mild meningitis and choroiditis has been reported; however, viral antigen was not detected in the choroid plexus with immunohistochemistry.…”
Section: The Brain Is a Major Target Of Niv Infection In Hamstersmentioning
confidence: 99%
See 2 more Smart Citations
“…22,87 A mild meningitis and choroiditis has been reported; however, viral antigen was not detected in the choroid plexus with immunohistochemistry.…”
Section: The Brain Is a Major Target Of Niv Infection In Hamstersmentioning
confidence: 99%
“…76 Hamsters have been immunized with NiV G and F glycoproteins expressed in vaccinia virus recombinants that induced an immune response and prevented fatal infection. 22 NiV and HeV sG is highly immunogenic in cats, mice, and rabbits, yielding homologous serum-neutralizing titers of greater than 1:20,000 in cats. 50 Complete protection from fatal NiV disease has been observed in 4 cats immunized three times with a 100-mg dose of recombinant HeV sG or with NiV sG.…”
Section: Antiviral Therapeutics and Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, NiV infections are much more widespread than previously recognized and so it is necessary to reevaluate strategies to prevent or treat this disease. We have recently shown that immunization with either one of the NiV glycoproteins (G [attachment protein] or F [fusion protein]) protects hamsters from a fatal infection (9). Further, passive administration of serum against either the G or F glycoprotein also protected the animals from a lethal challenge.…”
mentioning
confidence: 99%
“…The first study has shown that hamsters, vaccinated with vaccinia virus expressing either NiV F or G, were completely protected against NiV. Moreover, this group demonstrated that the naïve animals were also protected by passive transfer of hyperimmune serum prior to challenge (Guillaume et al, 2004). An important advance was next the development of a recombinant vaccine protecting pigs against NiV challenge (Weingartl et al, 2006).…”
Section: Vaccines and Treatmentsmentioning
confidence: 99%